SOSIALISASI TERAPI MENIUP BALON UNTUK MENGATASI SESAK NAPAS PADA PASIEN ASMA DI RUANG INSTALASI GAWAT DARURAT ( IGD ) RSUD KARAWANG - Serly , Serly; Yuli Herlina; Helza Herdiana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Asthma is a chronic airway disease characterized by bronchial narrowing due to inflammation and airway hyperresponsiveness, which causes symptoms of shortness of breath, coughing, and wheezing. Asthma management is not limited to the administration of bronchodilator medications but can also be assisted by non-pharmacological therapies such as breathing exercises. One simple and easy-to-do breathing exercise is balloon blowing therapy, which can help improve lung ventilation and reduce shortness of breath. The aim of this activity was to increase the knowledge and skills of patients and their families in balloon blowing therapy as an effort to overcome shortness of breath due to asthma. The activity method was carried out through socialization and direct demonstrations to patients and families in the emergency room of Karawang Regional Hospital. The results showed an increase in patient understanding of the correct balloon blowing technique and positive feedback regarding the ease of implementation of the therapy. In conclusion, the balloon blowing therapy socialization is effective as a simple educational tool to help asthma patients reduce shortness of breath independently.